Serious Delayed Hair Toe Tourniquet Syndrome with Bone Erosion and Flexor Tendon Lesion. (14th October 2014) - Bizzotto, Nicola; Sandri, Andrea; Regis, Dario; Carpeggiani, Guillherme; Lavini, Franco; Magnan, Bruno
Abstract : Hair toe tourniquet syndrome (HTTS) is an uncommon pediatric condition occurring when the toe is circumferentially strangulated by human hair or fibers. An 8-week-old little girl was admitted to the Emergency Department because of the worsening swelling in the right second and third toes, which had been been previously treated with a local antibiotic thinking of an infection. An unrecognized HTTS was leading the third toe to necrosis. An urgent release of the constricting band on the two toes was performed and bone erosion and partial flexor tendon lesion on the third toe were detected. We would like to raise awareness in the community and in colleagues about HTTS in children, because early recognition and urgent treatment are mandatory to provide an adequate management and prevent severe complications.